Pengaruh Corporate Financial Performance dan Corporate Social Responsibility terhadap Harga Saham Perusahaan - Puspithasari, Nidya; Sula, Atik Emilia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This research aims to analyze and provide empirical evidence of the influence of Corporate Social Responsibility, Return on Assets, Current Ratio, Total Asset Turnover, and Debt to Equity Ratio on the share prices of companies that have received the Asia Sustainability Reporting Rating award for 2020 - 2022 which are listed on the Stock Exchange Indonesian Effect. The method used is a quantitative method with secondary data types in the form of annual reports and sustainability reports. The sample selection technique used was purposive sampling with a total sample of 36. The analytical method used was multiple linear regression analysis. The research results show that partially Corporate Social Responsibility and Return on Assets have an effect on the company's share price, while the Current Ratio, Total Asset Turnover, and Debt to Equity Ratio have no effect on the company's share price. Simultaneously, Corporate Social Responsibility, Return on Assets, Current Ratio, Total Asset Turnover, and Debt to Equity Ratio do not have a significant effect on the company's share price.